Pemanfaatan Handphone dalam Pembelajaran Pendidikan Agama Islam di SMA Negeri 1 Baitussalam - Izzah, Nurul; Mahmud, Salami; Nurbayani, Nurbayani (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2026)
This study examines the optimization of mobile phones as an effective medium for Islamic Religious Education (PAI) learning at SMA 1 Baitussalam, Aceh, Indonesia, focusing on their benefits, challenges, and strategies to overcome obstacles in the digital era. Employing a descriptive qualitative method grounded in postpositivism, data were collected through triangulation techniques including observations, interviews, and documentation over two months. Participants included 3 PAI teachers, 12 eleventh-grade students, and the school principal. The findings reveal that mobile phones facilitate access to digital PAI textbooks, additional references like Qur'anic interpretations, Islamic educational apps (e.g., MyQuran, Google Classroom), discussion platforms, and educational videos on YouTube, promoting flexible and interactive learning aligned with the school's vision of faith, character, and global readiness. However, strict school regulations, including teacher supervision and sanctions, are implemented to prevent misuse, such as accessing social media or games. Key challenges include limited internet access and data quotas, distractions from notifications, and teachers' inadequate digital skills. To optimize mobile phones in PAI, recommendations include providing school internet facilities, teacher training in digital tools, and ethical guidelines for students. This research contributes practical insights for PAI educators, schools, and policymakers to integrate technology wisely, addressing gaps in PAI-specific digital education literature and supporting national educational goals amid globalization.